First records of Amblyomma geayi and Amblyomma varium (Ixodida: Ixodidae) parasitizing sloths in Nicaragua - Oporta López, Juan José (2025)
Ticks of the genus Amblyomma parasitize a wide variety of terrestrial vertebrate hosts, including humans. In Nicaragua, 14 species of ticks of the genus Amblyomma have been recorded. To our knowledge, no published records of ticks on sloths exist. However, A. varium, which parasitizes these hosts, was reported without an associated host. During 2023 and 2024, five sloths of two species (Bradypus variegatus and Choloepus hoffmanni) were rescued from four localities belonging to three Departments of Nicaragua. Two species of ticks were collected from the sloths, Amblyomma geayi and Amblyomma varium. Both records of ticks represent the first for Nicaragua in association with sloths. In this way, the richness of ticks of the genus Amblyomma in Nicaragua increases to 15 species.